Predictor of Obese Mothers and Stunted Children in the Same Roof: A Population-Based Study in the Urban Poor Setting Indonesia - Rachmah, Qonita; Mahmudiono, Trias; Loh, Su Peng (Frontiers in Nutrition, 2021)
Stunting leads to poor cognitive development, increase the risk of child mortality and elevate non-communicable diseases risks. This study aimed to determine the magnitude of double burden of malnutrition (DBM) in urban poor setting in Indonesia and investigate its predictors. This was a cross-sectional study involving 428 mothers proportionally chosen from 16 integrated health posts in Surabaya, Indonesia. The household were categorized into two groups based on mother’s body mass index (BMI) and child’s height-for-age z-score (HAZ); households without DBM and household with DBM. Energy, carbohydrate, protein and fat intake was obtained using 24-hours food recall and socioeconomic status was measured using a structured questionnaire. Data on socioeconomic status were: mother’s educational level and occupation, household income, and food expenditure. The prevalence of household with DBM was 27.5%; 12.4% pair stunted children and normal weight mother; 45.6% pair of overweight/obese mother and normal height children. Logistic regression analysis showed significant differences in the mother’s education level, mother’s occupation, protein intake of the children, and fat intake of the mother between households with and without double burden of malnutrition. This study offers an important insight to improve mother’s knowledge related to protein intake of children to reduce stunting risk.